An examination of the glaciomarginal fan of the Odranian glaciation at the Mokrzeszów site, Sudetic Foreland, SW Poland - Krzyszkowski, Dariusz; Wachecka-Kotkowska, Lucyna; Skurzyński, Jacek (Geology, Geophysics and Environment, 2022)
The article presents the results of research from the Mokrzeszów site in the Sudetic Foreland. Lithopetrographic and sedimentological analyses of sediments from the Middle Polish Glaciations (Early Saalian, Odranian, MIS6) in this area indicate the overrepresentation (90–95%) of large Scandinavian erratics. The deposits, representing a repetitive sequence of Gp-Gms-Sp-Sh/Sr(Dmm) lithofacies, accumulated during at least two episodes of glacial outburst floods and six sedimentary cycles. High-energy flows are estimated for the Gms and Gp facies at about 5 m∙s−1 and low-energy flows indicate 0.8 m∙s−1 for the Sp/Sh/Sr facies, to the lack of flow (Fm). The sedimentary sequences confirm the existence of a fan, which may have originated as a subaqueous steep coarse-grained fan in glacial-flow-lake-outburst floods that formed between the ice sheet front and the morphotectonic edge of the Sudetic Marginal Fault line and within the Roztoka-Mokrzeszów Graben, or as an aerial, piedmont fan on the Sudetic Marginal Fault edge. The sediments show discontinuous deformations – gently sloping faults and fractures from glacioisostatic stresses. The fault activity is probably related to the reactivation of the faults due to ice loading during or after the older Saalian glaciation.